Home advantage in professional soccer and betting market efficiency: The role of spectator crowds. (2nd March 2022) - Fischer, Kai; Haucap, Justus
Abstract: Fan support has often been considered to be a main driver of the home advantage in sports. Using the "natural exper‐ iment" of ghost games during the COVID‐19 pandemic in German professional soccer and a dataset of 6, 120 matches ranging over the seasons 2011/2012 to 2020/2021, we test this claim. Indeed, applying a difference‐in‐differences setup, we identify a reduction in the home performance ‐ though with much heterogeneity across leagues and teams. We, moreover, observe the home advantage to recover over time. In analysing whether betting markets anticipated this drop in the home advantage and its recovery, we test the efficient market hypothesis. In the short‐run, betting odds do not properly reflect the effect of ghost games regarding changes in the home advantage but they suitably account for it in the long‐run. Also, league heterogeneity is efficiently captured in the odds. Based on these findings, we show how simple, short‐run betting strategies could have exploited the discussed phenomenon. Our findings also have implications for agents' behavior on financial markets in the presence of unforeseen and unfamiliar shocks.